Determinants and Effects of Innovative Activities in Vietnam. A Firm-level Analysis - Hien Thu Tran; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper investigates the determinants of innovative activities and the innovation-performance relationship for the firm population in Vietnam in three consecutive stages: decision – investment – outcome. Cragg's two-tiered dynamic type-2 Tobit model and instrumental variable GMM method are applied to control for the selectivity and endogeneity of R&D and innovation. After controlling for ownership types, industry and regional fixed-effects, key findings include: (i) R&D and innovation activities not only stimulate firms' profitability and growth of sales, but also increase their survival propensity; (ii) private innovative firms significantly outperform their peers whereas the combination of young, small, and innovative characteristics in young innovative companies (YICs) does not bring the expected higher entrepreneurial performance as how it works in advanced countries; (iii) highly-leveraged firms, exporting firms, and diversified firms are more likely to be innovative than their counterparts, but the ability to transform innovative efforts into higher profitability and growth can only be witnessed among diversified firms; and (iv) firms being endowed with larger asset pool have more favorable conditions to engage in innovation activities, but do not necessarily produce superior performance relatively to their smaller counterparts. However, firm labor size is positively associated with both R&D intensity and entrepreneurial performance of firms. The dataset of population of existing firms (from 2000 to 2005) extracted from the annual enterprise survey conducted by Vietnam General Statistics Organization (GSO) is used for the empirical analysis.
Keywords: O32; O33; O53; L25; 330